New Zealand primary school teachers' preparedness to teach children with chronic illnesses : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Psychology at Massey University, Albany, New Zealand - Adams, Nicola Leigh (Massey University, 2018)
All children are entitled to good quality education where they can learn alongside their peers from qualified, registered, and well supported teachers. However, previous research suggests that some teachers are underprepared and inadequately resourced to meet the needs of children living with chronic illnesses and that this can exacerbate the academic and social challenges these children may face in an educational context. Using a mixed-methods approach, this study examined New Zealand primary school teachers’ preparation and experiences in teaching children with chronic illnesses. Fifty-five teachers responded to an online survey that gathered both quantitative and qualitative data. The results were further explored with a purposive nested sample (N = 4) using in-depth follow-up interviews. Seventy-eight percent of the survey respondents had not received any initial teacher education training with regards teaching children with chronic illnesses, and almost half (47%) had not undertaken any in-service professional learning and development. Information and supports available to teachers tended to have a specific focus on medical needs, with limited consideration for potential academic and social implications. Consistent with international findings, the results of this study indicate the need for improved teacher education, more readily accessible information and support, and further opportunities for interprofessional collaboration. The results extend on the international literature by highlighting a strength-based, family-centred approach to working with these learners. Teachers’ self-efficacy beliefs are identified as an important area for further research on this topic. Keywords: Childhood chronic illness, inclusive education, teacher education, primary school, mixed-methods, interprofessional collaboration, teacher self-efficacy
Keywords: Primary school teachers -- Training of -- New Zealand; Primary school teachers -- In-service training -- New Zealand; Primary school teachers -- New Zealand -- Attitudes; Chronically ill children -- Education, Primary -- New Zealand